Seismic Response of a Water Transmission Pipeline Across a Fault Zone Adopting a Large-Scale Vibration Table Test - Deng, Longsheng; Zhang, Wenzhong; Dai, Yan; Fan, Wen; Li, Yubo; Ren, Sen; Li, Pei (Frontiers in Earth Science, 2021)
The seismic response is generally amplified significantly near the fault zone due to the influence of discontinuous interfaces and weak-broken geotechnical structures, which imposes a severe geologic hazard risk on the engineering crossing the fault. The Hanjiang to Weihe River Project (Phase II) crosses many high seismic intensity regions and intersects with eight large-scale regional active faults. Seismic fortification of the pipelines across the fault zone is significant for the design and construction of the project. A large-scale vibration table test was adopted to investigate the seismic response and fault influences. The responses of accelerations, dynamic stresses, strains, and water pressures were obtained. The results show that the dynamic responses were amplified significantly by the fault zone and the hanging wall. The influence range of fault on acceleration response is approximately four times the fault width. The acceleration amplification ratio in the fault zone generally exceeds 1.35, even reaching 1.8, and the hanging wall amplification ratio is approximately 1.2. The dynamic soil pressure primarily depends on the acceleration distribution and is apparently influenced by pipeline location and model inhomogeneity. The pipeline is bent slightly along the axial direction, accompanied by expansion and shrinkage in the radial direction. The maximum tensile and compressive strains appear at the lower and upper pipeline boundaries near the middle section, respectively. Massive y-direction cracks developed in the soil, accompanied by slight seismic subsidence. The research findings could provide reasonable parameters for the seismic design and construction of the project.